Characterization of an Innovative Biomaterial Derived From Human Wharton’s Jelly as a New Promising Coating for Tissue Engineering Applications - Fayon, Adrien; Helle, Deborah; Francius, Gregory; Vincourt, Jean-Baptiste; Regnault, Véronique; Dumas, Dominique; Menu, Patrick; El Omar, Reine (Frontiers in Bioengineering and Biotechnology, 2022)
The extracellular matrix (ECM) offers the opportunity to create a biomaterial consisting of a microenvironment with interesting biological and biophysical properties for improving and regulating cell functions. Animal-derived ECM are the most widely used as an alternative to human tissues that are of very limited availability. However, incomplete decellularization of these tissues presents a high risk of immune rejection and disease transmission. In this study, we present an innovative method to extract human ECM derived from the Wharton’s jelly (WJ-ECMaa) of umbilical cords as a novel biomaterial to be used in tissue engineering. WJ-ECMaa was very efficiently decellularized, suggesting its possible use in allogeneic conditions. Characterization of its content allowed the identification of type I collagen as its main component. Various other matrix proteins, playing an important role in cell adhesion and proliferation, were also detected. WJ-ECMaa applied as a surface coating was analyzed by fluorescent labeling and atomic force microscopy. The results revealed a particular arrangement of collagen fibers not previously described in the literature. This biomaterial also presented better cytocompatibility compared to the conventional collagen coating. Moreover, it showed adequate hemocompatibility, allowing its use as a surface with direct contact with blood. Application of WJ-ECMaa as a coating of the luminal surface of umbilical arteries for a use in vascular tissue engineering, has improved significantly the cellularization of this surface by allowing a full and homogeneous cell coverage. Taking these results together, our novel extraction method of human ECM offers a very promising biomaterial with many potential applications in tissue engineering such as the one presented direct in vascular tissue engineering. Further characterization of the composition and functionality will help explore the ways it can be used in tissue engineering applications, especially as a scaffold or a surface coating.